Peranan Orang Tua Dalam Pendidikan Agama Kristen Terhadap Pertumbuhan Rohani Anak - Semuel Ruddy Angkouw; Simon Simon (Sekolah Tinggi Teologi Yerusalem Baru, Manado, 2020)
AbstractParents who are given a mandate by God to be the main spiritual educators for their children. The purpose of God is to encourage parents as the main spiritual educators for their children, so that their children will experience spiritual growth in their faith in Him. This paper discusses the role of parents in Christian religious education on children's spiritual growth. The method used in this writing is a quantitative method with a questionnaire approach accompanied by descriptions of the answers of the respondents to the questionnaires that were distributed. The findings of this study are the respondents, in this case the church Gereja Pantekosta di Indonesia (GPdI) Glenmore Kabupaten Banyuwangi, carry out its role as a parent in cultivating Christian values for the spiritual growth of children although not significantly overall.Key words: Spiritual Growth, Congregation, Christian Education. AbstrakOrang tua diberikan mandat oleh Allah untuk menjadi tenaga pendidik kerohanian yang utama bagi anak-anaknya. Tujuan Allah menghimbau orang tua sebagai pendidik kerohanian utama bagi anak, agar kerohanian anak mengalami pertumbuhan secara iman kepada-Nya. Tulisan ini membahas tentang peran orang tua dalam pendidikan agama Kristen terhadap pertumbuhan kerohanian anak. Metode yang digunakan dalam penulisan ini adalah metode kuantitatif dengan pendekatan angket disertai pendeskrifsian jawaban para responden atas angket yang dibagikan. Temuan dari penelitian ini adalah para respoden dalam hal ini jemaat Gereja Pantekosta di Indonesia (GPdI) Glenmore Kabupaten Banyuwangi, melaksanakan perannya sebagai orang tua dalam penanaman nilai-nilai kekristenan untuk pertumbuhan kerohanian anak walau tidak secara signifikan secara keseluruhan.Kata kunci: Pertumbuhan Rohani, Jemaat, Pendidikan Agama Kristen